Revitalizing the state of primary healthcare towards achieving universal health coverage in conflict affected fragile northeastern Nigeria: Challenges, strategies and way forward - Musa, Shuaibu S.; Ibrahim, Adamu M.; Ogbodum, Molly U.; Haruna, Usman A.; Gololo, Ahmed A.; Abdulkadir, Abdulafeez K.; Ukaegbu, Enyinnaya; Agyapong, Joseph; Shallangwa, Muktar M.; Adamu, Nuruddeen A.; Muhammad, Bello A.; Lucero-Prisno III, Don E. (Narra Sains Indonesia, 2024)
The Alma-Ata Declaration of 1978 defined primary healthcare as a critical way to obtain universal healthcare and 'health for all.' In Nigeria, the National Health Policy (NHP) and the subsequent formation of the Primary Health Care System aim to modernize healthcare delivery, at the grassroots level. In recent decades, however, the status of primary healthcare in Nigeria, particularly in the northeastern region, has significantly deteriorated, further posing significant threats to health equity and universal access to healthcare. Armed conflicts, humanitarian crises, insufficient finance, inadequate infrastructure, and labor shortages have negatively impacted the region's primary healthcare facilities. This article discusses the poor state of primary healthcare in northeastern Nigeria and its implications for achieving universal health coverage in the region. In addition, the article elaborates on the historical context, highlights the difficulties and challenges in the development of primary healthcare, and explores potential solutions to improve the system.